PENGEMBANGAN MODUL PEMBELAJARAN IPA SMP PADA MATERI TEKANAN BERBASIS KETERAMPILAN PROSES SAINS - Rosa, Friska Oktavia (Jurnal Pendidikan Fisika, 2015)
The aims of this reseach is to design and develop a science module based on science process skills and to test the effectiveness of the module to studentsâ learning achievement and motivation. This research is Educational Reseach and Development. The development of this module used 4D models. The stage are define, design, development and disseminate. Science module is developed using a model of integration connected. Modules which developed based on science process skills includes observing phase, classifying phase, communicating phase, measuring phase, predicting phase and concluding phase used on science process skills includes. The results showed that there were increasing students learning achievement and increasing studentsâ science process skills. Development of science-based KPS module consider effective because in addition to increasing student learning outcomes, science process skills of the students themselves have increased.